VigSatDB: genome-wide microsatellite DNA marker database of three species of Vigna for germplasm characterization and improvement. (31st May 2019) - Jasrotia, Rahul Singh; Yadav, Pramod Kumar; Iquebal, Mir Asif; Bhatt, S B; Arora, Vasu; Angadi, U B; Tomar, Rukam Singh; Jaiswal, Sarika; Rai, Anil; Kumar, Dinesh
Abstract: Genus Vigna represented by more than 100 species is a source of nutritious edible seeds and sprouts that are rich sources of protein and dietary supplements. It is further valuable because of therapeutic attributes due to its antioxidant and anti-diabetic properties. A highly diverse and an extremely ecological niche of different species can be valuable genomic resources for productivity enhancement. It is one of the most underutilized crops for food security and animal feeds. In spite of huge species diversity, only three species of Vigna have been sequenced; thus, there is a need for molecular markers for the remaining species. Computational approach of microsatellite marker discovery along with evaluation of polymorphism utilizing available genomic data of different genotypes can be a quick and an economical approach for genomic resource development. Cross-species transferability by e-PCR over available genomes can further prioritize the potential SSR markers, which could be used for genetic diversity and population differentiation of the remaining species saving cost and time. We present VigSatDB —the world's first comprehensive microsatellite database of genus Vigna, containing >875 K putative microsatellite markers with 772 354 simple and 103 865 compound markers mined from six genome assemblies of three Vigna species, namely, Vigna radiata (Mung bean), Vigna angularis (Adzuki bean) and Vigna unguiculata (Cowpea). It also contains 1976 validated published markers. Markers can be selected on the basis of chromosomes/location specificity, and primers can be generated using Primer3core tool integrated at backend. Efficacy of VigSatDB for microsatellite loci genotyping has been evaluated by 15 markers over a panel of 10 diverse genotype of V. radiata . Our web genomic resources can be used in diversity analysis, population and varietal differentiation, discovery of quantitative trait loci/genes, marker-assisted varietal improvement in endeavor of Vigna crop productivity and management.